Contemporary enzyme kinetics and mechanism - Purich, Daniel L. (Elsevier/Academic Press, 2009)
Kinetic studies of enzyme action provide powerful insights into the underlying mechanisms of catalysis and regulation. These approaches are equally useful in examining the action of newly discovered enzymes and therapeutic agents.